LECTURER’S VIEW ON PRAGMATIC ISSUE: PRAGMATIC FAILURE AND PRAGMATIC COMPETENCE - Rahmatul Khasanah; Yanti Rahayu Ningsih; Marveline Adelina Putri Siswanto (Politeknik Negeri Bengkalis, 2021)
Pragmatic is one of the important competencies that should be mastered by language learners because it focuses on utterance and speaker meaning. With regard to its focus, pragmatics deal with language functions-that is what language expression is commonly used in a particular situation. As language function, there are some aspects of pragmatics to be known by language learners during communication. However, this idea is not in line with the real condition because most English teaching in Indonesia does not focus on it. The aim of this research is to know the lecturer’s view on the pragmatic failures phenomenon, students’ pragmatic competence, and the way to solve producing pragmatic failures in communication.